WEAR PREDICTION USING GIWM (GLOBAL INCREMENTAL WEAR MODEL) METHOD - Jamari, Jamari (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2009)
Wear is very important parameter in an engineering design. A model for predicting the wear behaviour is presented in this paper. The model, which is called global incremental wear model (GIWM), is build upon an iterative procedure. This study considers the pin-on-disc sliding contact system. The model for computing wear on pin is based on the idea of successively computing the contact radius and thus the contact area due to the flattening of the spherical tipped pin. In order to verify the developed model, the results are plotted together with the published results. There are two publisher results, numerically and experimentally. Results show that the developed GIWM model predicts the wear behavior very well.